Language Learner Motivational Types: A Cluster Analysis Study. Issue 3 (September 2014) - Papi, Mostafa; Teimouri, Yasser
<x xml:space="preserve">Abstract</x> The study aimed to identify different second language (L2) learner motivational types drawing on the framework of the L2 motivational self system. A total of 1, 278 secondary school students learning English in Iran completed a questionnaire survey. Cluster analysis yielded five different groups based on the strength of different variables within their motivational configurations. Further analyses revealed that the motivational groups have different motivational, emotional, and linguistic characteristics. In the second part of the study, the sample was divided into promotion‐focus and prevention‐focus groups based on the self‐regulatory focus theory. Partial correlation analysis showed that while the ideal L2 self and instrumentality promotion were associated with motivated learning behavior for both the promotion‐focus and prevention‐focus groups, only the ought‐to L2 self and instrumentality prevention were associated with motivated behavior for the prevention‐focus group. The study highlights the importance of considering motivational types in L2 motivation research.